2017
DOI: 10.1099/ijsem.0.002044
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus caviae sp. nov., an obligately heterofermentative bacterium isolated from the oral cavity of a guinea pig (Cavia aperea f. porcellus)

Abstract: A Gram-stain-positive, facultatively anaerobic, and catalase- and oxidase-negative bacterial strain designated MOZM2T, having 98.4 % 16S rRNA gene sequence identity with Lactobacillus reuteri DSM 20016T, was isolated from a swab of the oral cavity of a home-bred guinea pig. Comparative analyses based on the hsp60, pheS and tuf genes confirmed L. reuteri as its closest relative species, with calculated sequence similarities of 92.8, 88.8 and 96.9 %, respectively. DNA-DNA hybridisation revealed a 42 % degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Multilocus sequence analysis has been increasingly used to identify and describe novel species ( Killer et al, 2014 , 2017 ; Chen et al, 2017 ; Doi et al, 2017 ; Liu et al, 2017 ; Ribeiro et al, 2017 ; Modesto et al, 2018 ). Mattarelli et al (2014) stated that a minimum of two additional phylogenetic markers should be used to accurately identify isolates, especially for describing novel species in the genera Bifidobacterium and Lactobacillus .…”
Section: Introductionmentioning
confidence: 99%
“…Multilocus sequence analysis has been increasingly used to identify and describe novel species ( Killer et al, 2014 , 2017 ; Chen et al, 2017 ; Doi et al, 2017 ; Liu et al, 2017 ; Ribeiro et al, 2017 ; Modesto et al, 2018 ). Mattarelli et al (2014) stated that a minimum of two additional phylogenetic markers should be used to accurately identify isolates, especially for describing novel species in the genera Bifidobacterium and Lactobacillus .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Killer et al [ 5 ] isolated a strain from the oral cavity of the guinea pigs (MOZM2T) that showed 98.4 % similarity to Lactobacillus reuteri DSM 20016 T . However, because of the difference in the cellular profiles of fatty acids between MOZM2T and Lactibacillus reuteri DSM DSM 20016 T , they proposed that their strain be considered a new taxon within the group of heterofermentative lactobacilli and named it Lactobacillus caviae sp.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing avenue for mitigating these challenges lies in the utilization of probiotic bacteria isolated from guinea pig intestines. Studies conducted by Killer et al [ 5 ] and Sechovcová et al [ 6 ] showcase the isolation of Lactobacillus caviae and Alloscardovia venturai, both belonging to the lactobacillus and bifidobacterium species respectively. Furthermore, Palakawong Na Ayudthaya [ 7 ] identified a Streptococcus species from guinea pig fecal samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant cellular fatty acids (>10%) of strain IM3328 T were C 16 : 0 (17.2%), C 18 : 1 ω9 c (46.1%) and summed feature 7 (23.1%). C 16 : 0 and C 18 : 1 ω9 c are generally considered as the dominant cellular fatty acids for lentilactobacilli strains [22]. The content of C 18:1 ω9 c could clearly differentiate strain IM3328 T from the reference strains.…”
Section: Full-textmentioning
confidence: 99%